THE ADOPTION OF FLY SWATTER GAME TO IMPROVE STUDENTS’ VOCABULARY MASTERY AT MTS HIFZIL QUR’AN MEDAN - Lubis, Siska Wulan Dari (BRIGHT VISION Journal of Language and Education, 2021)
This study was aimed to find out improving students’ vocabulary mastery by using Fly Swatter Game at Mts Hifzil Qur’an Medan. The study was conducted by using Classroom Action Research (CAR). The research was conducted into two cycles of action and consisted of four meetings for each cycle. The procedures of the research were planning, action, observation, and reflection. The sample of the research were the first grade of Mts Hifzil Qur’an Medan chosen by saturation sampling. Overall, the total number of the sample was 30 students consisting of all boys.Furthermore, the techniques of collecting the data were conducted by giving test, interviewing the students and the English teacher, observing the teaching and learning process, diary notes and documentation. The instruments used in this research were observation sheet, interview guidelines, diary notes and test. In analyzing the data, the researcher analyzed the quantitative data by using analytic scoring rubric and then comparing the mean score of the students’ writing scores.Meanwhile, the qualitative data were analyzed by making qualitative descriptions by Miles. The result of this research showed that the students’ vocabulary mastery especially in adjective could be improved through the use of Fly Swatter Game. The result of this research showed that there was improving of students’ vocabulary. The mean of pre-test was 47,80. The mean of post test 1 was 65,37. the mean of post-test 2 was 77,23. It indicated that the scores and the mean in second cycle were better than the first cycle. In other words, the students’ are more interest and motivate in vocabulary mastery during teaching and learning process. The students could pronounced the words correctly. Using Fly Swatter Game, the students were eager to study English. By using Fly Swatter Game the students could memorize and understand certain words. Key words: Fly Swatter Game, Vocabulary Mastery